The year of the dog / 1. - Lin, Grace (Year of the Dog, 2006)
Frustrated at her seeming lack of talent for anything, a young Taiwanese American girl sets out to apply the lessons of the Chinese Year of the Dog, those of making best friends and finding oneself, to her own life.